Doing action research a guide for school support staff - Taylor, Claire, 1968- (Supporting learning professionally., 2006)
This book acts as an introduction to research methods, and uses real case studies from practising teaching assistants in primary and early years settings. It provides an overview of the processes involved in action research, shows you how to identify an issue, design and carry out a course of action and evaluate the impact.